PERBANDINGAN DAYA TOKSISITAS BIOPESTISIDA BAWANG PUTIH (Allium sativum) DAN DAUN SIRSAK (Annona muricata) PADA HAMA TANAMAN KUBIS Plutella xylostella - Iwan Ridwan Yusup; Ukit Ukit (Gunung Djati Conference Series, 2021)
Plutella xylostella is a caterpillar pest that is found in many vegetables and requires control. One way to control pests naturally is done by making biopesticides. The purpose of this research is to compare the biopesticidal power of garlic and soursop leaves on Plutella xylostella with experimental methods and using an intermediate bacterium in the form of Lactobacillus caseii Shirota which is fermented together with the basic ingredients (garlic and soursop leaves). The research was conducted at the biology education laboratory of UIN Sunan Gunung Djati Bandung. The results of this study indicate that the toxicity of garlic-based biopesticides (Allium sativum) is higher compared to biopesticides made from soursop leaves (Annona muricata) with a mortality percentage of 87.5%. Based on this research, good biopesticides are used to overcome caterpillar pests on cabbage plants, namely biopesticides with the main ingredients of garlic, in addition to effective biopesticides are also more environmentally friendly.